Transport of pore-water oxygen with/without aeration in subsurface wastewater infiltration system - Wang, Siqi; Li, Yinghua; Li, Haibo; Yang, Lei (Water SA, 2019)
In this study, three subsurface wastewater infiltration systems (SWISs) at different aeration were set up to study the transport of pore-water oxygen and quantify the amount of trapped gas. Bromide and dissolved oxygen were introduced into SWISs as partitioning tracer and non-partitioning tracer, respectively. A model named CXTFIT based on the convection diffusion equation was used to describe the shape of breakthrough curves for bromide and dissolved air in column experiments. In CXTFIT code, the parameter β obtained from the bromide test ranging from 0.2940 to 0.7600 indicates that the physical non-equilibrium model was relatively suitable for dissolved air transport. Retardation factors obtained by CXTFIT code indicate 2–20% porosity filled with gas. Tracing the transport of air and determining the percentage of porosity filled with trapped gas has lain a foundation for further study on gas clogging in SWISs.